2021
DOI: 10.1101/2021.03.15.435449
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of substrate composition and exogenous hormone application on vegetative propagule rooting success of essential oil hemp (Cannabis sativaL.)

Abstract: To support the rapidly expanding industrial hemp industry, a commercial supply of high-quality starter plants with low genetic variability from nurseries will be key to consistent and efficient cultivation efforts. Rooting success was evaluated across four propagation medias, five rooting hormones, and eight commercially available high-cannabidiol (CBD) essential oil hemp cultivars. Cuttings were placed in a climate-controlled room and assessed for rooting success 12 days after cloning. Rooting success was det… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
1
1
1
Order By: Relevance
“…There was no significant difference in rooting success (P 5 0.16) between talc (88%) and IBA in solution (83%). These findings generally concur with those of Campbell et al (2021), who evaluated the effects of five different hormone treatments that included three different IBA formulations used in hemp propagation [Hormodin (OHP, Bluffton, SC), Hormex, Dip'N Grow (Dip'N Grow, Clackamas, OR)] and reported that the different rooting hormone treatments used had no significant differences in terms of rooting success. IBA formulation had a significant effect on quality for both shoots and roots (Table 2).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…There was no significant difference in rooting success (P 5 0.16) between talc (88%) and IBA in solution (83%). These findings generally concur with those of Campbell et al (2021), who evaluated the effects of five different hormone treatments that included three different IBA formulations used in hemp propagation [Hormodin (OHP, Bluffton, SC), Hormex, Dip'N Grow (Dip'N Grow, Clackamas, OR)] and reported that the different rooting hormone treatments used had no significant differences in terms of rooting success. IBA formulation had a significant effect on quality for both shoots and roots (Table 2).…”
Section: Resultssupporting
confidence: 86%
“…The 0-and 3000-ppm treatments both led to an average rooting percentage of 89%, whereas the average rooting percentage of the 8000-ppm treatment was reduced to 79%. This contrasts with Campbell et al (2021), who reported a 15-to 18fold increase in rooting with hormone compared with no hormone. IBA concentration had a significant effect (P < 0.001) on the quality scores of both roots and shoots (Table 2, Fig.…”
Section: Resultscontrasting
confidence: 75%
“…In 2018, hemp cultivation, implying Cannabis sativa plants with a THC level <0.3%, was legalized by the US government for the purpose of producing these secondary metabolites for recreational and medicinal purposes. 20,21 We recently demonstrated that THC levels escalated above the 0.3% regulatory threshold in several popular hemp cultivars during October. 22 This implies the existence of a harvest window of no later than September, and farmers of these cultivars must harvest their crop by then to be compliant, preventing embargo by regulatory authorities.…”
Section: ■ Introductionmentioning
confidence: 99%